Redefining Education in the Digital Economy: The Role of Social Innovation-based Learning in Information Systems Education - Abhari, Kaveh; Koobchehr, Farzan; Huxford, Cyrus; Olivares, Fernando; Kohsuwan, Pocky; Sosa, Luis (Assoc Information Systems, 2020)
Social responsibility is at the core of modern Information Systems (IS) education due to increased attention by society on the ethics, human factors, and social consequences of emerging technologies. With the acknowledgement that most IS education falls short along these areas, this paper sheds light on the application of Social Learning and Social Innovation-based Learning in socially responsible IS Education. The connectivism principles were used to develop a learning model based on social innovation that was then tested by the example of an upper-division course (Systems Analysis) at a state university. The case study results suggested that the proposed learning model can help students to not only see information systems as social systems but also consider themselves as catalysts for positive change enabled by these systems. The findings also confirmed the positive impact of the proposed intervention on students' social skills. This study contributes to the future of IS education by proposing social innovation-based learning as a practical education paradigm for the digital economy.
Keywords: Accès gratuit sur inscription; Digital; social; Éducation; États-Unis